The PROSES PEMBUATAN CETAKAN PIRING ORGANIK MENGGUNAKAN MESIN BUBUT KONVENSIONAL DAN CNC - Hermawati, Neni; Rachmat, Asep (Universitas Majalengka, 2021)
Abstract The increasing use of metals in the industrial world, including in terms of technology, plays an important role in easing the task of humans in making or shaping something. For example, metal forming and metalworking techniques range from conventional to non-conventional, such as in the process of making organic plate molds. Practitioner choose placement in the Organic Plate Mold Making Process because they want to know the cutting conditions of the pressing / bottom plate mold and the G-code used in making the cross-section / top plate mold. The plate mold making process uses conventional and CNC lathes. Conventional lathes are used to make top molds whereas CNC is used to make bottom molds. With the mold using a circular ST 37 steel with a thickness of 45 mm and a diameter of 260 mm. Then the undergoes a surface leveling process, then it is followed by a flat turning process, tapering until finishing. Then proceed with the blocking process so that the prints are smoother and more even. Keywords: Organic Plate Mold, Conventional Lathes, CNC.